Wokół poematu Meghadūta Kalidasy - Mejor, Marek (Gajt Wydawnictwo 1991 s.c., 2018)
The present article is dedicated to Professor Joanna Sachse whose Polish translation of Kālidāsa’s Meghadūta aroused much interest among the Polish Sanskritists in this masterpiece of the classical Sanskrit poetry. The paper consists of seven parts. In the first part there are collected references and accounts on the Meghadūta which are found in the 19th century Polish literature. The following part is devoted to the enumeration and description of the most important editions (and translations) of the Meghadūta and its commentaries; special attention is paid to the oldest dated palm-leaf Nepalese manuscript from 1363 A.D. In the third part of the paper there are discussed selected passages from the Sanskrit treatises on the theory of literature (kāvya) in which their author quoted some stanzas from Kālidāsa’s Meghadūta as an illustration of the formulated theses. The fourth part is devoted to the discussion of the meaning of the 14th stanza of the poem. According to two commentators, Dakṣināvartanātha and Mallinātha, the stanza has a double meaning, viz. the words ‘nicula’ and ‘diṅnāga’ may be understood as personal names – of a certain poet Nicula, and the Buddhist master Diṅnāga (Dignāga). The interpretation of the stanza has been subject to many speculations by the modern scholars who have struggled to combine the dates of Kālidāsa and Diṅnāga, having taken for granted the validity of such identification. In the following fifth part are contained two accounts on Kālidāsa’s life as found in the Sanskrit sources translated into Polish. The sixth part presents Kālidāsa and his poem Meghadūta in the Tibetan literary tradition. Finally, the seventh part tells about an old Sanskrit manuscript which was found in a remote Chinese Buddhist monastery. One folio of the manuscript contains a reference to Kālidāsa and to his three poems, viz. Kumārasambhava, Meghadūta and Raghuvaṃśa.
Keywords: Kālidāsa; Meghadūta; kāvya; Dignāga